2008
DOI: 10.1111/j.1537-2995.2008.01802.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatal group C streptococcal infection due to transfusion of a bacterially contaminated pooled platelet unit despite routine bacterial culture screening

Abstract: An asymptomatic donor was implicated as the source of GCS-contaminated PLTs. Current screening methods for PLTs are not sufficient to detect all bacterial contamination. Pooled PLTs are a particular challenge because the small volume of individual units places limits on culturing strategies. Improved detection of bacterial contamination of PLTs is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…SDSE was isolated from both the residual blood component bag and the recipient. A donor throat swab specimen collected 20 days after donation still contained SDSE [55]. These observations call for the implementation of improved safety measures for platelet concentrates.…”
Section: Perspectives Concerning Emerging Infectious Diseasementioning
confidence: 89%
See 1 more Smart Citation
“…SDSE was isolated from both the residual blood component bag and the recipient. A donor throat swab specimen collected 20 days after donation still contained SDSE [55]. These observations call for the implementation of improved safety measures for platelet concentrates.…”
Section: Perspectives Concerning Emerging Infectious Diseasementioning
confidence: 89%
“…Recently, fatal or near-fatal transfusion-transmitted infections involving platelet concentrates have been reported from some countries other than Japan [55][56][57]. SDSE was isolated from both the residual blood component bag and the recipient.…”
Section: Perspectives Concerning Emerging Infectious Diseasementioning
confidence: 99%
“…Bacterial culture technics present a risk of false-negative results attributed to time of incubation and period of sampling. Septic reactions after transfusion of PC unit despite this screening by culture have already been reported 16 17. Pathogen-inactivation techniques are new, promising methods that have demonstrated their efficacy in reducing unit contamination, and are progressively utilised in Europe 18…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of a false-positive result (which means, no microorganisms could be cultured from the bottle flagged positive) was about two-fold higher for the anaerobic bottles. of Platelet Concentrates in the Netherlands 253 However, based on reported cases [8][9][10], it is clear that falsenegatives occur, but no hard data on the frequency in regular screening could be derived from these reports. Recently, several studies reported on the frequency of false-negatives, one for apheresis PCs [11] and two for buffy coat-derived PCs [12,13], being around 0.1%.…”
Section: Rate Of Initial Positive Cultures In the Screeningmentioning
confidence: 98%